Caracterização radiográfica ex vivo de biomateriais utilizados para regeneração óssea em mandíbulas de porcos - Corbi, Samara Cruz Tfaile [UNESP]; Spin Neto, Rubens [UNESP]; Marcantonio Júnior, Elcio [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP] (My University, 2012)
Introduction: The radiographic characteristics of a biomaterial, such as its density, may influence the evaluation of the results obtained following its clinical use. Objective: The aim of this study was to evaluate the radiographic density of biomaterials used as bone substitutes, inserted into dental sockets and bone defects in created in the jaws of pigs. The influence of a soft tissue simulator on the results was also evaluated. Material and method: Two and three-millimeter-deep bone defects were created in the pigs mandible and the right first molar extraction socket were used. Commercial samples of five biomaterials were tested: Hydroxyapatite, Lyophilized Bovine Bone, 45S5 bioglass (generic), PerioGlass and β-Tri-Calcium Phosphate, and compared to a positive (mandibular bone) and negative (empty alveolar bone defects) controls. Radiographic images were acquired with and without a 10 mm thick soft-tissue simulator. Result: The results for the extraction sockets showed no differences between the biomaterials and the negative control. For the bone defects, the depth of the defect density influenced the density, both in the negative control (p < 0.01) and biomaterials (p < 0.05) groups. The soft- tissue simulator did not alter the results. Conclusion: The type of the evaluated defect can interfere in the radiographic features presented by each biomaterial, while the simulation of soft tissues was not statistically significant.

Introdução: As características radiográficas, como a densidade, podem influenciar na avaliação dos resultados obtidos com a utilização de biomateriais. Objetivo: O objetivo deste estudo foi avaliar a densidade radiográfica de diferentes biomateriais substitutos ósseos, inseridos em alvéolos dentários e defeitos ósseos, em mandíbulas de porcos, além de verificar a influência de simulador de tecido mole. Material e método: Foram obtidos os defeitos: defeitos ósseos de 2 e 3 mm de profundidade no ramo da mandíbula, e alvéolos originados da extração dos primeiros molares direitos. Foram utilizadas amostras comerciais de cinco diferentes tipos de biomateriais, todos granulados: Hidroxiapatita, Osso Bovino Liofilizado, Biovidro 45S5 (genérico), PerioGlass e β-Fosfato Tri-Cálcio, que foram comparados com controle positivo (região óssea mandibular sem defeito) e controles negativos (defeitos ósseos e alvéolos vazios). Tomadas radiográficas foram realizadas com e sem simulador de tecido de 10 mm de espessura. Resultado: Os resultados obtidos nos alvéolos não demonstraram diferenças entre o controle negativo e os biomateriais avaliados. Nos defeitos ósseos, a profundidade do defeito mostrou influenciar a densidade tanto nos grupos controle negativo (p < 0,01) como nos grupos de biomateriais (p < 0,05). O simulador de tecidos moles não alterou os resultados. Conclusão: Pode-se concluir que os tipos de defeitos avaliados podem interferir nas características radiográficas apresentadas pelo biomaterial, enquanto que a simulação de tecidos moles não se mostrou relevante estatisticamente.
Ex-vivo radiographic characterization of biomaterials used for bone regeneration in pig jaws
Keywords: Bone alveolus; Bone defect; Biomaterials; Radiography; Bone density; Pigs; Alvéolo ósseo; Defeito ósseo; Biomateriais; Radiografia; Densidade óssea; Porcos